Dispute Resolution in Islamic Economic Transactions: The Role and Function of Sharia Arbitration - Widjaja, Gunawan (Universitas Muhammadiyah Surakarta, 2025)
Dispute resolution in Sharia economic transactions is essential to align settlement processes with Islamic legal principles. This study examines the function and role of Sharia-based arbitration, focusing on its alignment with the values of justice, efficiency, and confidentiality within Islamic law. Using a literature-based methodology, the research analyzes secondary data from legal sources and previous studies on Sharia arbitration in Indonesia, particularly the practices of the Sharia Arbitration Body (BASYARNAS-MUI). The findings indicate that Sharia arbitration offers a streamlined, confidential, and fair dispute resolution method, fostering outcomes based on Islamic values such as justice (adl), truth (haqq), and public good (maslahat). Unlike conventional court procedures, Sharia arbitration provides faster and more effective resolutions, while ensuring privacy and protecting the involved parties' reputations. The study also reveals that Sharia arbitration strengthens the application of Islamic law across various sectors, including finance and inheritance, by embedding ethical considerations into modern economic dispute resolutions. This research underscores the practicality and moral alignment of Sharia arbitration as a robust alternative to conventional litigation, offering readers insights into the benefits of a Sharia-compliant approach to economic dispute resolution.